Из Именного указателя к «Записным книжкам» Ахматовой: Борис Пастернак. Часть I [From an Index to Anna Akhmatova’s _Notebooks_: Boris Pasternak. Part 1] - Timenchik, Roman (Slavica Revalensia, 2026)
This article is yet another installment in the series of Roman Timenchik’s annotations to Anna Akhmatova’s Notebooks. This particular installment concerns Boris Pasternak (1890—1960).